The current landscape for the treatment of mitochondrial disorders. (20th February 2018) - Slone, Jesse; Gui, Baoheng; Huang, Taosheng
Abstract: The mitochondrial organelle is crucial to the energy metabolism of the eukaryotic cell. Defects in mitochondrial function lie at the core of a wide range of disorders, including both rare primary mitochondrial disorders and more common conditions such as Parkinson's disease and diabetes. Inherited defects in mitochondrial function can be found in both the nuclear genome and the mitochondrial genome, with the latter creating unique challenges in the treatment and understanding of disease passed on through the mitochondrial genome. In this review, we will describe the limited treatment regimens currently used to alleviate primary mitochondrial disorders, as well as the potential for emerging technologies (in particular, those involving direct manipulation of the mitochondrial genome) to more decisively treat this class of disease. We will also emphasize the critical parallels between primary mitochondrial disorders and more common ailments such as cancer and diabetes.